Joint monitoring of chromatic dispersion, OSNR and inter-channel nonlinearity by LFM pilot. (April 2019) - Yang, Aiying; Guo, Peng; Wang, Wanli; Lu, Yueming; Qiao, Yaojun
Highlights: The CD, OSNR and inter-channel NL are monitored simultaneously by our method. The CD estimation precision is improved by zero padding at the receiver. The OSNR monitoring is insensitive to fiber NL. Accurate inter-channel NL monitoring is achieved. Abstract: A novel joint monitoring method is proposed for dynamic and reconfigurable optical transmission systems to estimate chromatic dispersion (CD), optical signal-to-noise ratio (OSNR) and inter-channel nonlinearity (NL) simultaneously. This method utilizes two linear-frequency modulation (LFM) pilots with different center frequencies at two polarizations. The CD is estimated by the peak position difference of two pilots in fractional domain. Compare to previous work of CD estimation, the monitoring precision of CD is improved by zero padding at the receiver. The OSNR and the inter-channel NL are obtained in frequency and fractional domain. By verification of 9-channel 28 GBaud wavelength division multiplexing QPSK and 16QAM systems after 1000 km transmission, it proves that this method achieves stable CD ( < 200 ps/nm error), nonlinearity tolerant OSNR and accurate inter-channel NL ( < 1 dB error) monitoring.